Characterization of polyaniline–Ag–rGO nanocomposites for saprophytic and pathogenic Leptospira bacteria detection in water - Abdullah, H.; Mahalingam, Savisha; Azami, N. H.; Bejo, Siti Khairani; Kamal, Noorfazila; Othman, Mohd Hafiz Dzarfan; Yuliarto, Brian; Yahya, Iskandar; Manap, Abreeza; Fatihah, S.; Abd Rahman, Norliza; Yuhana, Nor Yuliana; et al. (Springer, 2022)
This research aims to develop polyaniline (PANI)–Ag–rGO nanocomposite thin films to detect Saprophytic and Pathogenic Leptospira bacterias in water. The sol–gel method followed by a spin-coating technique was conducted in this work to synthesize nanocomposite thin films of PANI–Ag(1−x) –rGOx (x = 0.025, 0.050, 0.075, 0.100). The results revealed that PANI–Ag0.975–rGO0.025 thin film exhibited the most robust sensitivity, with the highest Ag concentration. The x-ray diffraction and field-emission scanning electron microscope analysis confirmed the structure of the nanocomposites with Ag nanospheres. The atomic force microscope study showed greater surface roughness for the nanocomposites with high Ag concentrations. Furthermore, PANI–Ag0.975–rGO0.025 nanocomposite possessed the highest electrical conductivity (2.81 Scm−1), which resulted in the excellent detection of Leptospira bacteria in water.